2021
DOI: 10.3389/fphar.2021.722283
|View full text |Cite
|
Sign up to set email alerts
|

TNF-α–Induced miR-21-3p Promotes Intestinal Barrier Dysfunction by Inhibiting MTDH Expression

Abstract: Intestinal barrier dysfunction is characterized by increased intestinal permeability to lumen endotoxin, showing remarkable predisposition to immune enteropathy, and colorectal cancer tumor necrosis factor (TNF)-α is associated with this pathological process, while the mechanism remains unknown. In this study, different doses of TNF-α were used for Caco-2 cell treatment. We discovered that miR-21-3p expression was obviously increased by TNF-α in a dose-dependent manner. Further study demonstrated that TNF-α co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…In recent years, a limited number of studies also confirmed that AEG-1 may be associated with barrier dysfunction. Jiang et al [26] found that upon TNF-a stimulation of CaCo2 cells, miR-21-3p expression was elevated, which directly targeted AEG-1 mRNA, consequently modulating intestinal barrier dysfunction. Another study revealed that inhibiting AEG-1 and its downstream pro-inflammatory cytokines mitigated blood-spinal cord barrier leakage and improved hind limb motor function during spinal cord ischemia-reperfusion [27].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, a limited number of studies also confirmed that AEG-1 may be associated with barrier dysfunction. Jiang et al [26] found that upon TNF-a stimulation of CaCo2 cells, miR-21-3p expression was elevated, which directly targeted AEG-1 mRNA, consequently modulating intestinal barrier dysfunction. Another study revealed that inhibiting AEG-1 and its downstream pro-inflammatory cytokines mitigated blood-spinal cord barrier leakage and improved hind limb motor function during spinal cord ischemia-reperfusion [27].…”
Section: Discussionmentioning
confidence: 99%
“…Although the underlying mechanism through which MG infection leads to TJ damage has not yet been fully elucidated, some studies have shown a close correlation between the suppression of TJ protein expression and an increase in proinflammatory mediators [ 41 ]. Jiang et al discovered that TNF-α acts as another key cytokine that coordinates tracheal epithelial damage in the context of MG infection and can activate the NF-κB pathway [ 42 ]. Growing evidence suggests that when exposed to pathogenic agents, the trachea experiences an increase in intracellular calcium ion levels.…”
Section: Discussionmentioning
confidence: 99%
“…MiRNA-21-3p has been recently shown to play a role in the regulation of the expression of tight junction proteins responsible for the integrity of the intestinal epithelial barrier in the GIT. A recent 2021 study demonstrates that TNF-α-induced expression of miRNA-21-3p caused decreased levels of metadherin (MTDH) [72]. MTDH is a negative regulator of the Wnt signalling pathway.…”
Section: Tnf-α/ Wnt Signalling Pathway As a Regulator Of Intestinal B...mentioning
confidence: 99%